Devising a methodological approach to determining priorities for digital transformation of transport enterprises - Vorobiov, Yevhenii; Palyvoda, Olena; Tarnovska, Iryna (Eastern-European Journal of Enterprise Technologies, 2026)
The process that improves decision-making for prioritizing the implementation of digital technologies at a transport enterprise under the conditions of uncertainty associated with war and European integration has been investigated in this study. The objective need to improve the efficiency of decisions is predetermined by resource constraints faced by enterprises, especially under conditions of martial law. To solve the problem, it has been proposed using a methodological approach based on the hierarchy analysis method. A system of criteria for assessing the priority of digital technologies for transport enterprises was built, which consists of the following groups: economic, technological, organizational-managerial, social-security, and strategic. It was established that the most significant criteria for evaluating digital technologies for the studied enterprises are operational stability (0.4214), technological reliability (0.2621), physical security of infrastructure (0.2987), management flexibility under risk conditions (0.4237), protection of life and health of employees (0.4593), as well as compliance with the legislation of Ukraine and EU norms (0.2713). The priority of implementing digital technologies for the studied group of transport enterprises was justified based on the construction of a multi-criteria model and the application of the Analytic Hierarchy Process. The following digital technologies were considered to be of the highest priority: transport monitoring and telematics systems, electronic document management, digital contracts and digital interaction platforms. The objectivity and consistency of the results is attributed to the fact that the evaluation was based on substantiated criteria that provided a multidimensional reflection of the impact of digitalization on the activities of enterprises. A feature of the improved methodological approach is its higher universality. It is suitable for practical application in various modes of transport and for a wide continuum of digital technologies